Implementation of Tourism Activities on MFN (Most-Favoured- Nation Treatment) and (NT) National Treatment Principle - Kadek Apriliani; I Dewa Ayu Devi Maharani Santika (Warmadewa Press, 2022)
This study aims to find out the principles of Most Favored Nation (MFN) and National Treatment (NT) in the Provisions of Law of the Republic of Indonesia Number 10 of 2009 concerning Tourism. This type of research is normative legal research with a statutory approach. The research materials used are primary and secondary by connecting problems from various sources, literature studies into data collection techniques and data processing systematically and logically and analyzed with perspective analysis methods. In accordance with the formulation of the problem, this research is to examine the principles of Most Favored Nation (MFN) and National Treatment (NT) contained in the Provisions of Law of the Republic of Indonesia Number 10 of 2009 concerning Tourism.